Nanotechnology for intracellular nucleic acid delivery - Zhang, Ke (Henry Stewart Talks, 2015)
Using nucleic acids as therapeutics, Nucleic acid delivery systems, Nucleosome mimicking polymer particles, Cationic shell-crosslinked knedel-like nanoparticles (cSCKs), High density spherical nucleic acids (SNAs), Hollow SNAs